Motivational orientations for participation in educational development programs among primary school teachers from SK. Siburan Batu, St. George Punau, St Patrick Semedang and SK Sira Krian in Padawan District / Annyta Anchang Alok - Alok, Annyta Anchang (2007)
The teacher’s competence is crucial in ensuring successful primary schools in Padawan District and Sarawak in general. Therefore, it is important to understand the motivational orientations for participation in educational development programs among the primary school teachers and the motivational orientation factors which influence their participation in educational development programs that are conducted by the Educational authorities. This study aims to determine the motivational orientations for participation in educational development programs among the primary school teachers and the motivational orientations factors that influence their participation. A survey questionnaire was used to elicit information from the primary school teachers of the four selected schools. The finding shows an overwhelming indication that the primary school teachers of the mentioned school s perceived a high motivational orientations for participation in Educational development programs regardless of their age, experience, academic qualification, school characteristics, social relationship and personal factors.